2018
DOI: 10.3390/nano8090715
|View full text |Cite
|
Sign up to set email alerts
|

Wall Thickness of Industrial Multi-Walled Carbon Nanotubes Is Not a Crucial Factor for Their Degradation by Sodium Hypochlorite

Abstract: The propensity of multi-walled carbon nanotubes (MWCNTs) for biodegradation is important for their safe use in medical and technological applications. Here, we compared the oxidative degradation of two samples of industrial-grade MWCNTs—we called them MWCNT-d and MWCNT-t—upon their treatment with sodium hypochlorite (NaOCl). The MWCNTs had a similar inner diameter but they differed about 2-fold in the outer diameter. Electron microscopy combined with morphometric analysis revealed the different degradation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
8
1
Order By: Relevance
“…On the other hand, the recent study by Newman et al demonstrated 39 that the wall thickness of MWNTs is not a crucial factor for their degradation by NaClO, which is in contrast with our results. By comparing the morphological changes occurring in two different types of NaClO-treated MWNTs by TEM, they found that thicker MWNTs became degraded on the outside wall and inner sidewall, while thinner MWNTs became degraded only at the inner sidewall.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the recent study by Newman et al demonstrated 39 that the wall thickness of MWNTs is not a crucial factor for their degradation by NaClO, which is in contrast with our results. By comparing the morphological changes occurring in two different types of NaClO-treated MWNTs by TEM, they found that thicker MWNTs became degraded on the outside wall and inner sidewall, while thinner MWNTs became degraded only at the inner sidewall.…”
Section: Discussioncontrasting
confidence: 99%
“…The authors suggested that the biodegradation of CNTs likely depends not only on the wall thickness but also on defects in the inner wall. 39 Our studies were performed at a higher temperature, and therefore the reaction rates were much faster than the rates reported in that study. 39 We did not find that oxidation of MWNTs with NaClO occurred only at the surface or at both the surface and the inner wall.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The biodegradation mechanism of CNTs is thought to involve oxidation by hypochlorous acid that is generated during enzymatic reaction 19–22 , and sodium hypochlorite or hypochlorous acid have since been shown to oxidize and degrade CNTs 2428 . Interestingly, 2D graphene oxide sheets are degraded faster than 1D oxidized CNTs 29 , and the wall thickness of CNTs might be not a crucial factor for their degradation by hypochlorite 30 . However, it is still not obvious whether CNTs are completely degraded.…”
Section: Introductionmentioning
confidence: 99%
“…To study the struc-tural modifications of CNTs, a CNT dispersion solution (100 mg/L) was ultrafiltered using a 10-kDa molecular weight cutoff membrane and rinsed with water before and after NaClO treatment for 1, 3, and 24 h. Transmission electron microscopy and Raman spectroscopy were used to characterize the collected CNTs. Additionally, the study discovered that graphene oxide could be an intermediate product of single-walled CNT degradation, implying that CNT degradation may require an unzipping mechanism compared with CNT oxidation using a strong acid treatment [63]. However, the reaction rates using sodium hypochlorite were considerably higher than those using a strong acid; moreover, no obvious nanoribbon structures were discovered.…”
Section: Other Technologiesmentioning
confidence: 99%